Premature Rupture of Membrane - A Clinical Study In Comilla Medical College Hospital - Nazneen, Shahela; Begum, Farhana; Nargis, Shakila (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To find out the sociodemographic characteristics, complications of pregnant woman with premature rupture of membrane (PROM) and asses the outcome of it. Materials and Methods: This prospective study was carried out at the department of Obstetrics & gynaecology of Comilla Medical College Hospital (CoMCH) from January 2009 to December 2009. All pregnant women admitted with PROM during this period were taken as study population. After taking proper history they were categorized as term or preterm PROM on the basis of duration of gestation estimated from 1st day of last menstrual period (LMP), previous antenatal records, clinical examination & also previous ultrasonography (USG) reports. Out of sociodemographic characteristics age distribution and gravidity were noted. Diagnosis was done on the basis of examination and investigations. All the women with PROM were then followed up, management was given according to protocol and caesarean section was performed according to indication. Birth weight and Apgar score of newborns were noted after delivery. Results: There were 198 cases of PROM recorded among 3142 admitted obstetrical patients over one year period. The hospital incidence of PROM was found to be 6.3%. Among them, 57.6% patients were admitted at term and 42.4% patients came before 37 completed weeks of gestation. Most of the pregnant women were between 20-24 years of age (54%), 41% were primigravida (59%) were multigravida. About 48.5% women presented with different complications associated with PROM. Among which 15.7% patients had oligohydramnios, 8.5% patients presented with chorioamnionitis suggested by culture report of high vaginal swab. Urine for culture and sensitivity was also done. About five (5.2%) developed premature labour before 37th week of gestation. About 10% women developed obstetric complications (failed trial) associated with medical diseases. Seventy seven patients were delivered by caesarean section, 16.2% vaginally, 4.04% patients responded to conservative management and 2.5% patients were referred to tertiary centre for extreme prematurity with associated complicating factors. Most of the babies (38.4%) were born with birth weight between 2.1- 2.5kg and 10.3% babies were less than 1.5kg. Conclusion: Term PROM was more in comparison to PPROM and most of them were multigravida. Caesarean section rate was high. Most common complication of was subclinical urogenital infection (53%) next oligohydramnios (25%) & (13.5%) women presented with chorioamnionitis. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 82-87